2021
DOI: 10.3390/v13081554
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Delays Apoptotic Cell Death Induced by Siniperca chuatsi Rhabdovirus in Epithelioma Papulosum Cyprinid Cells

Abstract: Autophagy and apoptosis are two key cell fate determination pathways, which play vital roles in the interaction between viruses and host cells. Previous research had confirmed that one strain of fish rhabdoviruses, Siniperca chuatsi rhabdovirus (SCRV), could induce apoptosis and autophagy after infection. In the current study, we continued to analyze the interaction of autophagy and apoptosis in SCRV-infected EPC cell lines after treatment with different autophagy or apoptosis inhibitors. We found that SCRV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our previous report demonstrated that SCRV could induce mitochondrial apoptosis in EPC cells by increasing caspase-3 and caspase-9 activities, downregulating MMP, and increasing intracellular ROS [17]. Given its central role in cell apoptosis, MMP loss is a marker of mitochondrial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous report demonstrated that SCRV could induce mitochondrial apoptosis in EPC cells by increasing caspase-3 and caspase-9 activities, downregulating MMP, and increasing intracellular ROS [17]. Given its central role in cell apoptosis, MMP loss is a marker of mitochondrial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…EPC cells were treated with EF-24 and SCRV viruses at different exposure sequences for 12 h and 24 h. Total RNA samples of the treated cells were extracted according to an experimental procedure recommended by the reagent kit manufacturer (Beijing Tsingke Biotech Co., Ltd., Beijing, China) and then reverse-transcribed into cDNAs. PCR experiments were performed using the following primer sequences: N-F. ATCCATCAGATCACAGAACGC, N-R: TCCCAGCCATTCTCCTCAGTCC, 18s-F: CATTCGTATTGTGCCGCTAGA, 18s-R: CAAATGCTTTCGCTTTGGTC [17]. The thermal cycling conditions were as follows: predenaturation (30 s at 95 • C), followed by 40 extension cycles (10 s at 95 • C, 15 s at 60 • C), and solubility curves (15 s at 95 • C, 60 s at 60 • C, 15 s at 95 • C).…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy mainly plays a survival role in adapting to unfavorable growth conditions or subsequent cell stress ( 133 ). It is mainly involved in differentiation, development, pathogen defense, aging, apoptosis and cell death ( 134 , 135 ). Autophagy plays a significant role in cell protection under physiological conditions ( 136 ).…”
Section: Potential Molecular Mechanism Of Mitochondrial Dysfunction I...mentioning
confidence: 99%